Finding the Early Identity for Children in the Film of Laskar Pencerah - Adiprabowo, Vani Dias; Widodo, Agung (Universitas Jambi, Indonesia, 2023)
This research aims to reveal the message in the film 'Laskar Pencerah'. It provides an overview of the wider community and how non-formal education can provide alternatives and educational inspiration through the learning community. It uses descriptive qualitative to build the meaning of the message in the film 'Laskar Pencerah' and to understand the phenomenon by describing it in words. In collecting data, it uses observations viewed through the YouTube channel. The data are used to explore the meaning of the film's story, explain, give, and detail the film's message. Furthermore, the research shows that the main character of a child who wants to continue to learn although limited in his life to achieve what he aspires to with continuous efforts. His efforts and hard work shape the child's character and help him find his identity early on.